Observing Solvent Dynamics in Porous Carbons by Nuclear Magnetic Resonance : Elucidating molecular-level dynamics of in-pore and ex-pore species. Issue 2 (1st April 2020) - Cervini, Luca; Barrow, Nathan; Griffin, John
The adsorption and diffusion of species in activated carbons is fundamental to many processes in catalysis and energy storage. Nuclear magnetic resonance (NMR) gives an insight into the molecular-level mechanisms of these phenomena thanks to the unique magnetic shielding properties of the porous carbon structure, which allows adsorbed (in-pore) species to be distinguished from those in the bulk (ex-pore). In this work we investigate exchange dynamics between ex-pore and in-pore solvent species in microporous carbons using a combination of one-dimensional (1D) and two-dimensional (2D) NMR experiments. We systematically compare the effects of four variables: particle size, porosity, solvent polarity and solvent viscosity to build up a picture of how these factors influence the exchange kinetics. We show that exchange rates are greater in smaller and more highly activated carbon particles, which is expected due to the shorter in-pore‐ex-pore path length and faster diffusion in large pores. Our results also show that in-pore‐ex-pore exchange of apolar solvents is slower than water, suggesting that the hydrophobic chemistry of the carbon surface plays a role in the diffusion kinetics, and that increased viscosity also reduces the exchange kinetics. Our results also suggest the importance of other parameters, such as molecular diameter and solvent packing in micropores.